Erythrocyte parameters, anemia conditions, and sex differences are associated with the incidence of contrast-associated acute kidney injury after coronary angiography - Li, Xihong; Chen, Qingqing; Yang, Xinrui; Li, Duanbin; Du, Changqing; Zhang, Jun; Zhang, Wenbin (Frontiers in Cardiovascular Medicine, 2023)
Objective Contrast-associated acute kidney injury (CA-AKI) is a critical complication when applying contrast medium, and the risk factors of CA-AKI have not been fully clarified. This study aimed to explore the relationships of CA-AKI with erythrocyte parameters, anemia conditions, and sex differences in patients after coronary angiography (CAG). Methods In this retrospective study, 4,269 patients who underwent CAG were enrolled. CA-AKI was defined as an increase in plasma creatinine of at least 0.5 mg/dl (44 μmol/L) or 25% within 72 h after exposure to the contrast medium. Three erythrocyte parameters, including hemoglobin, hematocrit, and red blood cell (RBC) count, were collected on admission. Logistic regression analyses were used to examine the associations of sex differences and erythrocyte parameters with CA-AKI in the overall population, restricted cubic splines to visualize these associations flexibly. Moreover, stratified and sensitivity analyses were conducted to assess the robustness of the findings. Results Overall, the mean (± standard deviations) age of patients was 67.05 ± 10.77 years, and 759 subjects (17.8%) developed CA-AKI. The results showed L-shaped relationships between erythrocyte parameters and CA-AKI incidence in each model (all P < 0.001). The incidence of CA-AKI was positively associated with the severity of anemia, while it showed no significant differences among the types of anemia. Moreover, female patients undergoing CAG had a higher risk of CA-AKI than male patients. Mediation analysis verified that erythrocyte parameters exerted an indirect effect on the sex differences of CA-AKI incidences. Conclusion In conclusion, females, perioperative anemia conditions, and lower erythrocyte parameters (hemoglobin, hematocrit, and RBC count) were verified as risk factors of CA-AKI in patients undergoing CAG. Furthermore, lower erythrocyte parameters among females exerted indirect effects on the sex differences in CA-AKI incidence.